Effects of Localized Arm Fatigue, General Fatigue, and Elbow Bracing on Shooting Accuracy and Shoulder Proprioception: A Randomized Crossover Study - Şırayder, Ukbe; Yılmaz, Oğuzhan (The European Research Journal, 2026)
Objectives: This study aimed to comparatively investigate the effects of localized arm fatigue, general fatigue, and elbow brace use on proprioceptive accuracy and shooting accuracy in amateur female basketball players. Methods: Fifty-two amateur female basketball players (mean age: 23.08±2.02 years) participated in a randomized crossover study. Participants underwent three experimental conditions: localized arm fatigue, general fatigue, and brace application, each tested on separate days with a 48-hour washout period between sessions. Proprioceptive accuracy was assessed using the Joint Position Sense Error (in degrees), and shooting accuracy was evaluated based on shot success percentage. Fatigue perception was measured using the Borg Rating of Perceived Exertion Scale. Statistical analyses included Friedman and Wilcoxon signed-rank tests with Bonferroni correction for multiple comparisons. Results: Localized arm fatigue significantly decreased shooting accuracy (from 53.16% to 38.83%, P=0.014) and increased proprioceptive error (from 5.40° to 8.65°, P=0.003). General fatigue resulted in a moderate increase in proprioceptive error (from 4.05° to 5.35°, P=0.049) but did not significantly affect shooting accuracy (P=0.090). The use of an elbow brace improved proprioceptive accuracy (error reduction from 5.30° to 3.00°, P=0.035) and marginally enhanced shooting performance (increase from 48.33% to 54.83%, P=0.027). Strong negative correlations were found between proprioceptive degradation and shooting accuracy after localized fatigue (r= –0.787, P